Observing elections the Commonwealth's way : the early years : the integrationist - Dundas, Carl W. (Ian Randle KingstonJM, 2007)
Focuses on the Commonwealth's way of observing elections from the very first mission, but emphasizes the observation programme that commenced in 1990 and continued through to 2000. Identifies some of the lessons that can be learnt from the observers' work during the period under consideration.